ANALYSIS OF SHORT STORY WRITING SKILL BY USING INTERACTIVE MULTIMEDIA BASED ON THE RELIGIOUS CHARACTER OF STUDENTS PRIMARY SCHOOL GRADE 6 - Cerianing Putri Pratiwi; Fauzatul Ma’rufah Rohmanurmeta (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
Interactive multimedia here is a learning medium that combines text, amber, audio. Interactive multimedia based on religious characters here is an interactive multimedia which contains the value of religious characters. The purpose of this study is to determine the ability to write short stories using interactive multimedia based on religious characters of grade 6 elementary school students. This research was a qualitative descriptive study. Verbal data in this study are the results of recording short story writing using interactive multimedia based on religious characters and nonverbal data, namely the value of the evaluation results of the ability to write short stories of grade 6 students using interactive multimedia based on religious characters. Subjects in this study were students of grade 6 Kawedanan 2 State Elementary School, totaling 39 people. This study uses data collection techniques, namely (a) observation, (b) interviews, and (c) tests. Data in this study will be analyzed with interactive data analysis techniques, namely data reduction, data presentation, and conclusion drawing. Based on the results of the evaluation given, students' short story writing skills are good. All students have achieved the Minimum Completion Criteria that has been set, namely 75. In learning to write short stories, the average grade is 82.18% of the total 39 students. The lowest value is 75 and the highest value is 90.